Peran Manajemen Sekolah dalam Mewujudkan Pendidikan Karakter Perspektif Imam Al-Ghazali - Safparudin, Safparudin; Furqon, Muhammad; Zuhdi, Ahmad; Tania, Inggrid; Marhamah, Marhamah (Universitas Indraprasta PGRI Jakarta, 2024)
Character education is an important issue in the world of education today. One of the Islamic thinkers who paid great attention to character education was Imam Al-Ghazali. In his view, character education is an essential aspect of forming a complete human being. This article examines the role of school management in and most importantly in realizing character education from Imam Al-Ghazali's perspective. Al-Ghazali, as one of the great Islamic scholars, emphasized the importance of morals and character in education. This research uses qualitative methods with a literature study approach to analyze Al-Ghazali's view on character education and how it is implemented in school management. The aim of this research is to provide practical recommendations for school principals, teachers, and other stakeholders in implementing holistic and sustainable character education based on the principles taught by Imam Al-Ghazali. Successful implementation of character education in schools can contribute to the formation of a better society. Therefore, it is important for every school to continue improve the quality of character education through effective and innovative school management.